Business Ethics as Field of Teaching, Training and Research in Oceania - Gustavson, Royston (2011)
Oceania is a diverse region consisting of 29 countries, all of which are islands; its total population is approximately 379 million people. Business Ethics is firmly established as an academic field in the region’s two OECD countries, Australia and New Zealand, and in Singapore, is still developing in a dozen other countries, but no development at all has been found in half of the region’s countries, including each of those that has no higher education institutions. A major task for Business Ethics in this region is to seed the development of the field in countries in which development has not yet begun, and to assist development where it is nascent. The key change to the focus of academic business ethics in this region over the past 15 years has been a shift in focus from the organisation and its employees, to business’ impact on the natural environment and external stakeholders.
Keywords: Papua New Guinea; Oceania; New Zealand; Indonesia; Fiji; Australia; Sustainability; Stakeholders; Corporate Social Responsibility; Corporate Governance; Business Ethics